Temporal trend of cancer mortality in a Brazilian state with a medium Human Development Index (1980–2018) - Lima, Marcela Sampaio (Sci Rep, 2020)
Emerging economy countries in epidemiological transition have been especially challenged in the fight against cancer. This was an ecological study that aimed to describe the temporal trend of cancer mortality in a Brazilian northeastern state with a medium Human Development Index using official Brazilian mortality data from 1980 to 2018. We calculated the mortality crude rate (CR) and age-standardized rate (ASR) based on official population counts and estimates. The Joinpoint Regression Program, National Cancer Institute, USA, was used to calculate time trends of cancer mortality. There were 34,214 deaths from cancer, excluding nonmelanoma skin cancer, in Sergipe. The overall cancer mortality ASR was 70.1 and 57.9 per 100,000 men and women, respectively. For the last five years, the leading causes of cancer deaths were prostate (21.3), trachea, bronchus and lung (11.7), stomach (6.5), oral cavity (5.4) and liver and intrahepatic bile ducts (5.1) in males and breast (13.8), trachea, bronchus and lung (6.6), cervix (6.4), colon/rectum (5.8) and central nervous system (3.6) in females. In addition, there was a significant reduction in deaths from ill-defined causes in the series. Our results show that although there has been an increase in cancer mortality rates associated with Western lifestyles, such as prostate, breast and colon/rectum, high rates of cancer related to poverty and infections, such as stomach and cervix, still persist in Sergipe.